Broadening the resource base for entrepreneurship education through teachers' networking activities. (April 2015) - Ruskovaara, Elena; Pihkala, Timo; Seikkula-Leino, Jaana; Järvinen, Minna Riikka
Abstract: The purpose of this paper is to examine the activities of vocational education teachers when networking in entrepreneurship education. The study examines how the background characteristics of the teachers and their participation in planning and training activities explain the level of use of external stakeholders. As a method, a linear regression analysis has been used. The data consists of 448 Finnish vocational education and training (VET) teachers. The results show that the teachers' business background or work experience does not lead to richer practices regarding utilizing different external stakeholders. However, teachers that participated in school or regional-level entrepreneurship education planning or training utilize external stakeholders significantly more than their colleagues. Highlights: This study focuses on VET teachers' networking in entrepreneurship education. The article stresses effects of background and participation in planning and training. Female teachers seem to be more bound to use externalities in their teaching. Teachers participated in planning or training cooperate more with external stakeholders. Conception of teachers' personal capability is positively related to networking activities.